Numerical Reconstruction in Maritime Archaeology - Smiljko Rudan; Šimun Sviličić; Davor Bolf; Irena Radić Rossi (Journal of Marine Science and Engineering, 2023)
Numerical reconstruction is the process of modeling, analyzing, and evaluating the performance of structures or a sequence of events using the finite element method and other numerical engineering methods. Although numerical analysis is used extensively in contemporary engineering problems, it can be equally useful in the study of ancient structures and events of the past. The materials and design of structures are different, e.g., when comparing a modern containership with an old galleon, but the main problem to be solved is essentially the same—will the ship sail efficiently and safely for many years? This paper aims to provide an overview of recent achievements in numerical reconstruction in maritime archaeology. Since it is clearly an interdisciplinary activity, research is often carried out within a specific project by project team members or interested groups of researchers. While the paper aims to provide a comprehensive overview of such efforts, special attention is paid to activities related to the AdriaS (Archaeology of Adriatic Shipbuilding and Seafaring) and NEREAS (Numerical Reconstruction in the Archaeology of Seafaring) projects supported by the Croatian Science Foundation, to which the authors actively contribute.